2020
DOI: 10.1017/jfm.2020.981
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanisms of second-mode instability in hypersonic boundary layers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…For hypersonic flows, porous coatings have been proven to be a promising passive control strategy for the second mode. Tian & Wen (2021) showed that the effect of the porous coating on the second mode was to distort the phase of mean temperature gradient effect at Mach 6 and reduce the internal energy growth induced by wall-normal transport. This mechanism resembles that of wall heating inferred from figure 5( b ).…”
Section: Results Of Rpamentioning
confidence: 99%
See 4 more Smart Citations
“…For hypersonic flows, porous coatings have been proven to be a promising passive control strategy for the second mode. Tian & Wen (2021) showed that the effect of the porous coating on the second mode was to distort the phase of mean temperature gradient effect at Mach 6 and reduce the internal energy growth induced by wall-normal transport. This mechanism resembles that of wall heating inferred from figure 5( b ).…”
Section: Results Of Rpamentioning
confidence: 99%
“…Figure 6 showed the effect of the porous coating on the oblique first mode at Mach 3.5. The same boundary condition as Tian & Wen (2021) is imposed, where is the wall acoustic admittance. When the wall changes from smooth () to porous (), the growth rate of the most unstable oblique first mode increases from to .…”
Section: Results Of Rpamentioning
confidence: 99%
See 3 more Smart Citations